D-galactose-induced animal model of male reproductive aging - Sulistyoningrum, Evy (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Aging is a complex biological process involving molecular, cellular and organic changes. Aging process is not merely caused by chronological age but it can be accelerated by environmental factors contributes to oxidative stress. Aging in male reproductive system is characterized by many conditions such as terticular atrophy, decreases testicular function of spermatogenesis, decreased testicular function of testosteron production which can lead to a serious clinical condition, infertility. Management of male infertility with excellent outcome is still a challenge and therefore new strategies need to be examined. Because of difficulties and ethical issues in human research, animal models of male reproductive aging are useful research tools for this purpose. Rodent models of male reproductive aging are the first choice because similarity of metabolism system and short lifespan. D-galactose animal model for aging seems to be closer to human aging of male reproductive system. It is an advantageous model for testing potencies of pharmacological agent and natural compounds on aging.